Manajemen SDM Sekolah dalam Meningkatkan Mutu Pembelajaran di SMAS Sabilillah Sampang - Munib Munib; Febri Susilawati (AL -ALLAM, 2026)
Human resource management serves as the fundamental pillar for building a productive, adaptive, and sustainable organization. In the modern work ecosystem, human resources are no longer viewed merely as a cost component but as strategic assets capable of creating competitive value. Based on this premise, the study addresses three issues: First, how teacher human resource development is implemented at SMAS Sabilillah Sampang. Second, the efforts made by teachers to enhance the quality of instruction at SMAS Sabilillah Sampang. Third, the evaluation processes and Follow-Up Plans (RTL) aimed at improving instructional quality at SMAS Sabilillah Sampang. This study employs a qualitative approach with a descriptive research design. Data were gathered through interviews, observations, and documentation. Informants included the school principal, teaching staff, and students.